Research on the influence of stress on the penetration behavior of hydraulic fracture: Perspective from failure type of beddings - Yuesong Bai; Yuesong Bai; Yaoqing Hu; Xingchuan Liao; Jin Tan; Yongxiang Zheng; Wei Wang (Frontiers in Earth Science, 2023)
The failure types of bedding determine the penetration behavior of hydraulic fracture. A stratum model containing bedding was established based on the 3D block distinct element method to explore the penetration behavior of hydraulic fractures with different types of bedding. The mechanics of hydraulic fractures penetrating the shear- failure bedding plane and tensile-failure bedding plane were analyzed. The results showed that the shear-failure bedding plane was more difficult to expand than the tensile-failure bedding plane after the hydraulic fracture turns to bedding plane. The initial stress magnitude controls the expansion difficulty of hydraulic fractures, and the high stress magnitude attenuated penetration behavior. The vertical stress affected the shear failure by increasing the shear strength of the bedding plane. It affected the tensile failure by increasing the initiation stress of the bedding plane. The effect of horizontal stress on the penetration behavior included the influence on the initiation stress of vertical joints and the enhancement of the interference stress on the horizontal bedding plane. The conclusions can provide the guidance for hydraulic fracturing in reservoir with bedding planes.